(untitled) (Transport systems and technologies, 2018)
In the work the physical concept was first established, definitions was given, formalized and the study of the dual wedge-shaped frictional wear of brake blocks was started. A new scientific approach and a method of research of a problem, which is connected with dual frictional wedge-shaped wear of brake pads, is revealed due to the presence of an edge top shear erosion . This is formed during the train movement from imperfection of the braking system. The causes of uneven wear of brake pads, which lead to the slopeof the brake pads and the pressure of the upper slack in the moving object of braking(wheel) are investigated.The results of geometrical and kinetostatic studies with the joint operation of the brake pad and the wheel are presented. The causes and onsequences of the acceleratedthe dual wedge-shaped wear of the brake pads on the pendulum suspension in the carriagesof freight cars were established. The braking of wheels in one-way and two-way motion was taken into account. A new principle for improving the frictional brakingmethod is proposed. This principle allows to predict the wear of pads, depending on the run of cars in operating conditions. It is proved that the angle of coverage g of the brake pad is reduced by the duality ofthe pad. This leads to an increase in the specific pressure in the upper part and lowerpressure in the lower part of the pads, which increases the operating costs of freighttransport on the rail.